An evolutionarily-unique heterodimeric voltage-gated cation channel found in aphids - Amey, Joanna S.; O'Reilly, Andrias O.; Burton, Mark J.; Puinean, Alin M.; Mellor, Ian R.; Duce, Ian R.; Field, Linda M.; Wallace, B.A.; Williamson, Martin S.; Davies, T.G. Emyr (Wiley, 2015)
We describe the identification in aphids of a unique heterodimeric voltage-gated sodium channel which has an atypical ion selectivity filter and, unusually for insect channels, is highly insensitive to tetrodotoxin. We demonstrate that this channel has most likely arisen by adaptation (gene fission or duplication) of an invertebrate ancestral mono(hetero)meric channel. This is the only identifiable voltage-gated sodium channel homologue in the aphid genome(s), and the channel's novel selectivity filter motif (DENS instead of the usual DEKA found in other eukaryotes) may result in a loss of sodium selectivity, as indicated experimentally in mutagenised Drosophila channels.